Quality of Work Life of Private Sector Banks Employees: A Discriminant Analysis - Gupta, B; Hyde, AM; Chhabra, I (International Journal of Computer Sciences and Engineering, 2025)
Introduction: Quality of Work Life (QWL) has emerged as one of the most important aspect of Job that ensures long term association of the employees with the organization. Quality of Work Life refers to the favourableness or unfavourableness of a work environment for the employee. Purpose: This research work aimed at exploring the key factors which absolutely predict and discriminate High QWL and Low QWL perceiving employees. Design and Methodology: The study is broadly based on primary data collected from 207 employees of Private Banks in Indore by using convenient sampling. Discriminant analysis was applied to know which factors absolutely predict High QWL Perceiving employees and Low QWL perceiving employees with the help of SPSS. Results – The study reveals that factors of QWL like ‘healthy working environment’, ‘motivational climate’, ‘productivity’, ‘work redesign’, ‘sense of accomplishment’ ‘Employees’ Democracy’ ,and ‘stimulating work environment’ are significantly differentiated between High QWL perceiving employees and Low QWL perceiving employees. Implications- Quality of work life covers various aspects under the general umbrella of supportive organizational behavior. The outcome of this research is beneficial for policymakers, planners and development economists to formulate effective strategy of human resource development in Banking sector and other similar sectors.